Ezra Pound’s Poetry between Victorianism and Modernism: A Historical-Biographical Analysis - Abdulqadr , Kezhan Salar; Omer, Roz Jamal; Sharif, Ranjdar Hama (Technium Social Sciences Journal, 2021)
This paper examines the short poems of Ezra Pound, a group of works that have long been the subject of academic discussion in the field of literary analysis. Although Ezra Pound is typically considered a Modernist poet, some clear elements of Victorianism can be discerned within his revolutionary forms of poetry. The paper will offer a historical and biographical background to Pound’s work before moving on to an analysis and discussion of the poet’s short poems. While previous studies of Ezra Pound’s poetry have adopted various critical approaches, we believe that this is the first study that compares the influence of Modernism and Victorianism on the work of this important figure in English verse of the early twentieth century.